Edukasi Ibu Hamil Dalam Mempersiapkan Generasi Bebas Stunting Di Kelurahan Pakis - Sendy Firza Novilia Tono; Dianita Primi Hastuti; Shinta Wurdiana Romadona; Intiyaswati Intiyaswati; Devi Aprilia (Pelita Abdi Masyarakat, 2021)
Background : WHO states that stunting is an index of PB/U or TB/U with a limit value (z-score) less than -2 Standard Deviation. The causes of stunting are divided into 2 periods, namely the antenatal period and the postnatal period. Stunting begins in utero and continues for at least the first 2 years of the postnatal period. Basic Health Research Data (Riskesdas) shows that the prevalence of stunting in Indonesia in 2018 was 30.8%. Judging from these data, it is necessary to increase maternal knowledge about stunting so that children are not at risk of stunting. Stunting can cause growth and development disorders and increase the risk of morbidity and mortality. Types of Activities by conducting counseling methods so that groups of pregnant women in the region produce a generation free from stunting. Method : The location of this Community Service Activity is located in Pakis Village with the target being 30 pregnant women. The stages of the Community Partnership Program activities are divided into three stages, namely preparation, implementation, and monitoring stages. Results : Based on the community service that has been carried out, it is found that there is an increase in knowledge of pregnant women about stunting. This activity is expected to help make the 1000 HPK program a success so that it is not too late to prevent problems. Conclusion : The results of counseling to groups of pregnant women in the region increase knowledge about stunting prevention